Advanced fabrication approaches to controlled delivery systems for epilepsy treatment. (2nd September 2018) - van Tienderen, Gilles Sebastiaan; Berthel, Marius; Yue, Zhilian; Cook, Mark; Liu, Xiao; Beirne, Stephen; Wallace, Gordon G.
ABSTRACT: Introduction : Epilepsy is a chronic brain disease characterized by unprovoked seizures, which can have severe consequences including loss of awareness and death. Currently, 30% of epileptic patients do not receive adequate seizure alleviation from oral routes of medication. Over the last decade, local drug delivery to the focal area of the brain where the seizure originates has emerged as a potential alternative and may be achieved through the fabrication of drug-loaded polymeric implants for controlled on-site delivery. Areas covered : This review presents an overview of the latest advanced fabrication techniques for controlled drug delivery systems for refractory epilepsy treatment. Recent advances in the different techniques are highlighted and the limitations of the respective techniques are discussed. Expert opinion : Advances in biofabrication technologies are expected to enable a new paradigm of local drug delivery systems through offering high versatility in controlling drug release profiles, personalized customization and multi-drug incorporation. Tackling some of the current issues with advanced fabrication methods, including adhering to GMP-standards and industrial scale-up, together with innovative solutions for complex designs will see to the maturation of these techniques and result in increased clinical research into implant-based epilepsy treatment. Abbreviations : GMP: Good manufacturing process; DDS(s): Drug delivery system(s); 3D: Three-dimensional; AEDs: Anti-epileptic drugs; BBB: Blood brain barrier; PLA: Polylactic acid; PLGA: Poly(lactic-co-glycolic acid); PCL: poly(ɛ-caprolactone); ESE: Emulsification solvent evaporation; O/W: Oil-in-water; W/O/W: Water-in-oil-in-water; DZP: Diazepam; PHT: Phenytoin; PHBV: Poly(hydroxybutyrate-hydroxyvalerate); PEG: Polyethylene glycol; SWD: Spike-and-wave discharges; CAD: Computer aided design; FDM: Fused deposition modeling; ABS: Acrylonitrile butadiene styren; eEVA: Ethylene-vinyl acetate; GelMA: Gelatin methacrylate; PVA: Poly-vinyl alcohol; PDMS: Polydimethylsiloxane; SLA: Stereolithography; SLS: Selective laser sintering.